LEGAL PROTECTION OF THE FREEDOM TO USE THE HIJAB AS A RIGHT TO RELIGIOUS FREEDOM: CASE STUDY OF THE HOSPITALITY INDUSTRY IN THE SAMARINDA CITY REGION - Pratama, Rio Arif; Sariayana, Tiya Manikam (NOMOI Law Review, 2024)
This study examines the legal protection against the prohibition of hijab for female workers in hotels located in Samarinda City. The research aims to analyze the legal protections available for women wearing hijabs and to determine whether such prohibitions constitute a violation of the right to worship. The research used in this research is empirical juridical with a statutory and case study approach. The findings reveal that the ban on hijabs in hotels results in violations of human rights and the religious rights of female workers. Although there are regulations in place to protect the right to worship, their implementation in practice remains weak, leaving female workers often in vulnerable positions. The study concludes that there is a need for strengthened regulations and legal awareness among employers to ensure that workers' rights are respected and protected, and to create an inclusive and equitable work environment